PENGARUH KONTESTASI POLITIK DESA TERHADAP KONFLIK AHMADIYAH DI GEGERUNG-LOMBOK BARAT - Baihaqi, Mohamad (Jurnal Sosiologi Agama, 2020)
The dynamics of the political elite that contestated in local elections have created the potential for conflict vertically. This condition has caused violence between religious groups. In the various cases of existing conflicts, sentimental religion is easy to become a major factor. But so many studies have only put the potential of conflict and the way of peace. This paper examines a pattern of relationships performed by the local political elite in its participation in political contestations. The political elite created the issue as the main means of generating violence. Using a qualitative approach and being supported with primary and secondary data sources comes from interviews and library data. The author wants to see how in the influence of political issues in creating violence in the Ahmadiyah congregation in West Lombok's Gegerung. Using qualitative data analysis, the study used an elite point of view as well as its behaviour. However, at the same time the study also found a new point of view that people with traditional localities are easy to make with the issue. In the end, this study found the importance of religious ability that is owned by the community was influential to resist the occurrence of violence on behalf of religion. So religion is not easy to be politicized.